PENYEDIAAN FASILITAS DAN KEBIJAKAN GUNA PENERAPAN CONJUGAL VISIT SEBAGAI SOLUSI DARI MASALAH PENYIMPANGAN SEKSUAL NARAPIDANA PADA LEMBAGA PEMASYARAKATAN DI INDONESIA - Firyal Arribah Syafiqoh; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Conjugal visits or visits of legal partners is a visit related to the biological needs of convicts who are married as one of the fulfillment of the needs for the prisoners. Biological needs or sex needs are one of the basic needs for humans listed in the rules of human rights both nationally and internationally. In this case prisons in Indonesia have not been able to fully implement the regulations regarding conjugal visits clearly or there is no policy regarding the implementation of regulations and the provision of conjugal visit room facilitation which can later be applied to all correctional institutions in Indonesia, so that it has an impact on the fulfillment of the rights of inmates as complete human beings, especially biological needs. Prisoners behind bars struggle to maintain their physical and mental health to defend the rights that they should get by nature as human beings. This study uses a normative juridical approach. The research is focused on examining the application of the rules or norms in positive law, this research method is carried out with data collection techniques carried out by literature studies.